Effectiveness of Legal Protection on Heirs in Dispute on Sale and Purchase of Inherited Land - Muhammad Rizky Eka Pratama; Bambang Tri Bawono; Amin Purnawan; R. Sugiharto (Sultan Agung Notary Law Review, 2022)
The purpose of this study is to find out and analyze: 1) The legal consequences of a dispute over the sale and purchase of inherited land without the consent of the heirs. 2) The effectiveness of legal protection for heirs in disputes over the sale and purchase of inheritance land against the law in Surabaya. The approach method used in this study is an empirical juridical approach. The specification of the research used is descriptive analytical research. This type of data uses primary and secondary data. The data analysis method used qualitative data analysis. The results of the study concluded: 1) The legal consequences of the dispute over the sale and purchase of inheritance land without the consent of the heirs are that the land is sold by people who are not entitled to sell it (because those who now hold ownership rights to the land are the heirs), therefore the sale and purchase cancelled. As a result of the law with the cancellation of the sale and purchase, the sale and purchase is considered to have never existed, and each party is returned to its original state before the "sale and purchase" event occurred, in which the ownership rights to the land remain with the heirs. This is in accordance with Article 1471 of the Civil Code which explains that buying and selling other people's goods is void, and can provide a basis for reimbursement of costs, losses and interest, if the buyer does not already know that the goods belong to someone else. 2). The effectiveness of legal protection for heirs in disputes over the sale and purchase of inheritance land against the law in Surabaya, namely considering that there are still disputes over the sale and purchase of inherited land, the effectiveness of legal protection for heirs in Surabaya needs to be increased through socialization from the Land Agency (BPN) to the public, especially experts. heirs to register their inheritance land with BPN, as an effort to provide protection to heirs in order to avoid inheritance rights disputes which must be carried out against the law where the result of an unlawful act is loss. Efforts to protect the law on disputes over the sale and purchase of inherited land without the consent and knowledge of the heirs, the legal heirs or holders of legal property rights over the inherited land can file a lawsuit to the Court.